Risk factor identification and prediction models for prolonged length of stay in hospital after acute ischemic stroke using artificial neural networks - Yang, Cheng-Chang; Bamodu, Oluwaseun Adebayo; Chan, Lung; Chen, Jia-Hung; Hong, Chien-Tai; Huang, Yi-Ting; Chung, Chen-Chih (Frontiers in Neurology, 2023)
Background: Accurate estimation of prolonged length of hospital stay after acute ischemic stroke provides crucial information on medical expenditure and subsequent disposition. This study used artificial neural networks to identify risk factors and build prediction models for prolonged length of stay based on parameters at the time of hospitalization. Methods: We retrieved the medical records of patients who received acute ischemic stroke diagnosis and were treated at a stroke center between January 2016 and June 2020, and a retrospective analysis of these data was performed. Prolonged length of stay was defined as a hospital stay longer than the median number of days. We applied artificial neural networks to derive prediction models using parameters associated with length of stay that were collected at admission, and a sensitivity analysis was performed to assess the effect of each predictor. We applied five-fold cross-validation and used the validation set to evaluate the classification performance of the artificial neural network models. Results: Overall, 2240 patients were enrolled into this study. The median length of hospital stay was 9 days. One thousand one hundred one patients (49.2%) had a prolonged hospital stay. A prolonged length of stay is associated with worse neurological outcomes at discharge. Univariate analysis identified 14 baseline parameters associated with prolonged length of stay, and with these parameters as input, the artificial neural network model achieved training and validation areas under the curve of 0.808 and 0.788, respectively. The mean accuracy, sensitivity, specificity, positive predictive value, and negative predictive value of prediction models were 74.5%, 74.9%, 74.2%, 75.2%, and 73.9%, respectively. The key factors associated with prolonged length of stay were National Institutes of Health Stroke Scale scores at admission, atrial fibrillation, receiving thrombolytic therapy, history of hypertension, diabetes, and previous stroke. Conclusion: The artificial neural network model achieved adequate discriminative power for predicting prolonged length of stay after acute ischemic stroke and identified crucial factors associated with prolonged hospital stay. The proposed model can assist in clinically assessing the risk of prolonged hospitalization, informing decision-making, and developing individualized medical care plans for patients with acute ischemic stroke.